(untitled) (Global Journal of Human-Social Science, 2016)
LED Fluorimeter has been used to measure the uranium content of the ground water samples of Bathinda District of South Punjab.16 locations have been selected for the present investigation. The aim behind this study is to see the variation in the uranium content of the ground water during 2012-2016 and to assess the radiological and chemical risk due to the uranium present through ingestion. The uranium concentration of the water samples of the studied villages varies from 9.72 to 186.61 μgl -1 with an average value of 69.54 μgl -1 .This uranium content exceeds the safe limit of 60 ppb of uranium in groundwater proposed by AERB, India.